Superantigen staphylococcal enterotoxin C1 inhibits the growth of bladder cancer - Liu, Tao; Li, Lin; Yin, Lei; Yu, Hongyuan; Jing, Hongwei; Liu, Yang; Kong, Chuize; Xu, Mingkai (Bioscience, biotechnology, and biochemistry, 2017)
Superantigens can induce cell-mediated cytotoxicity preferentially against MHC II-positive target cells with large amounts of inflammatory cytokines releasing. In this study, superantigen staphylococcal enterotoxin C (SEC) 1 was investigated to evaluate its potential in bladder cancer immunotherapy in vitro and in vivo. Our results revealed that SEC1 could stimulate the proliferation of human peripheral blood mononuclear cells (PBMCs) in a dose-dependent manner, accompanied with the release of interleukin-2, interferon-γ, and tumor necrosis factor-α, and increased the population of CD4 + T cells and CD8 + T cells. PBMCs stimulated by SEC1 could initiate significant cytotoxicity towards human bladder cancer cells in vitro. The results of in vivo antitumor experiment indicated that SEC1 could decrease the rate of tumor formation and prolong the survival time of tumor-bearing mice. Our study demonstrated that SEC1 inhibited the growth of bladder cancer. And it is also suggested that SEC1 may become a candidate for bladder cancer immunotherapy.